Exploring Digital Media as a Source of Aural Vocabulary Growth among Young EFL Learners in Papua - Adelce Sisilia Ferdinandus; Niko Kobepa; Benyamin Marotno (Prominent, 2026)
Limited access to authentic English input remains a persistent challenge in English-as-a-Foreign-Language (EFL) contexts, particularly in underrepresented regions such as Papua, Indonesia. This study examines the potential of digital media as an alternative source of aural vocabulary exposure among young EFL learners. Thirty-five first to third-grade students from SD YPPK Gembala Baik Abepura in Jayapura participated in a survey on English-language media engagement, accompanied by a lexical analysis of five YouTube channels' Cocomelon, Peppa Pig Asia, Ryanâ's World, KreekCraft, and Vlad & Niki. The findings demonstrate that children's frequent interaction with these media sources introduces a broader lexical repertoire than that typically encountered in school-based materials. High-frequency words are predominantly associated with daily routines, emotions, and interpersonal interaction, while technology- and entertainment-related terms appear as emergent categories linked to digital environments. The results suggest that digital media serve as a complementary channel of incidental vocabulary learning, contributing to the development of aural receptive knowledge in early language acquisition. These findings hold implications for EFL curriculum design and the development of vocabulary assessment instruments tailored to multilingual contexts in Papua.